Analisis dan Perbaikan Dwelling Time Menggunakan Metode Six Sigma DMAIC Pada Proses Importasi di PT. XYZ - Ihdinassayyida Eliza; Tranggono (Jurnal Serambi Engineering, 2025)
Dwelling time is the time required for import containers since the container is unloaded from the time the ship docks until it leaves the port area or Temporary Storage Area (TPS). This research aims to analyse and improve the dwell time in the import process at PT XYZ using the Six Sigma DMAIC (Define, Measure, Analyze, Improve, Control) methodology. The DMAIC approach is used to identify the root causes of high dwell time in the project during the period July 2021 to June 2022 and to design effective improvement solutions. The results of the study showed that one of the main factors causing the problem was the late delivery of shipping documents by the supplier. Based on the calculation of DPMO and Sigma value, it is found that the average Defect Per Million Opportunities (DPMO) is 107208.99 and the average Sigma value is 2.75, which is categorised into Sigma level 2. Therefore, it is claimed that the sigma value is still far from the desired value of 6, so long term improvements are needed for the smooth running of the next project to achieve the national dwell time target of 3 days.